2007
DOI: 10.1016/j.febslet.2007.04.034
|View full text |Cite
|
Sign up to set email alerts
|

ERp57 interacts with conserved cysteine residues in the MHC class I peptide‐binding groove

Abstract: The oxidoreductase ERp57 is a component of the major histocompatibility complex (MHC) class I peptide-loading complex. ERp57 can interact directly with MHC class I molecules, however, little is known about which of the cysteine residues within the MHC class I molecule are relevant to this interaction. MHC class I molecules possess conserved disulfide bonds between cysteines 101-164, and 203-259 in the peptidebinding and a3 domain, respectively. By studying a series of mutants of these conserved residues, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…1a,c). Studies by others have also detected ERp57-MHC class I disulfide-bonded dimers, and implicated ERp57 in the reduction of sub-optimally folded MHC class I prior to its degradation [15,16,17]. In support of this hypothesis, our findings show that the level of the ERp57-D b conjugate (not including tapasin) is enhanced by the absence of β 2 m, likely due to hampered D b folding.…”
Section: Resultssupporting
confidence: 87%
“…1a,c). Studies by others have also detected ERp57-MHC class I disulfide-bonded dimers, and implicated ERp57 in the reduction of sub-optimally folded MHC class I prior to its degradation [15,16,17]. In support of this hypothesis, our findings show that the level of the ERp57-D b conjugate (not including tapasin) is enhanced by the absence of β 2 m, likely due to hampered D b folding.…”
Section: Resultssupporting
confidence: 87%
“…ERp57 is covalently associated with the chaperone tapasin in the peptide‐loading complex, and participates in the stabilization of empty MHC class I molecules and in the selective loading of high‐affinity peptides 43. Antoniou et al 44 discovered that ERp57 had a direct access to the peptide‐binding groove of MHC class I molecules during assembly. MHC class I molecules bind and present short peptides to CD8 + T lymphocytes, enabling the detection and elimination of infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that PDIA3 plays an important role in endogenous antigen presentation. Antoniou et al (2007) reported that PDIA3 molecules can directly insert into the peptide binding groove of the MHC class I molecules to bind with them during the course of MHC molecules antigen-presenting, making the antigen binding groove more bindable for antigen peptides (Santos et al, 2007; Stepensky, Bangia & Cresswell, 2007), resulting in increased binding stability between MHC molecules and antigen peptides.…”
Section: Discussionmentioning
confidence: 99%